2021
DOI: 10.1038/s41598-021-84828-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrins and extracellular matrix proteins modulate adipocyte thermogenic capacity

Abstract: Obesity and the metabolic disease epidemic has led to an increase in morbidity and mortality. A rise in adipose thermogenic capacity via activation of brown or beige fat is a potential treatment for metabolic diseases. However, an understanding of how local factors control adipocyte fate is limited. Mice with a null mutation in the laminin α4 (LAMA4) gene (KO) exhibit resistance to obesity and enhanced expression of thermogenic fat markers in white adipose tissue (WAT). In this study, changes in WAT extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 55 publications
3
8
2
Order By: Relevance
“…These characterizations are consistent with the observation that adipose in knockout mice is more similar to beige adipose tissue. Overall, these observations align with findings that the absence of laminin α4 leads to changes in stromal cell distribution in pericapillary niches within adipose tissue [ 59 ]. The resulting data can be used to guide studies into understanding the mechanisms underlying the effect of laminin α4 on adipose tissue function.…”
Section: Resultssupporting
confidence: 88%
“…These characterizations are consistent with the observation that adipose in knockout mice is more similar to beige adipose tissue. Overall, these observations align with findings that the absence of laminin α4 leads to changes in stromal cell distribution in pericapillary niches within adipose tissue [ 59 ]. The resulting data can be used to guide studies into understanding the mechanisms underlying the effect of laminin α4 on adipose tissue function.…”
Section: Resultssupporting
confidence: 88%
“…However, evidence for semaphorin-mediated promotion of adipose tissue fibrosis is limited to a single study on Sema3C [121], while the impact of pro-fibrotic genes in adipocyte thermogenesis is still poorly understood [122,123]. Speculatively, cleaved Sema4B could act on pre-adipocytes or mature adipocytes to promote fibrosis, to trigger a range of negative impacts on adipocyte physiology like on adipose tissue plasticity and insulin resistance [121] or thermogenesis [124].…”
Section: Discussionmentioning
confidence: 99%
“…There have also been recent experiments exploring potential extracellular components that regulate thermogenic capacity and the conversion of white adipose tissue towards beige adipose tissue. It has been shown that ASCs induced towards a beige lineage when on top of Collagen 1A1, Collagen 3A1, and Laminin A4 had lower levels of Uncoupling Protein 1 (UCP-1) (a critical component for the regulation of brown/beige adipose tissue) compared to those differentiated on uncoated dishes [ 121 ]. In the absence of the Laminin A4 gene, thermogenic markers were upregulated in white adipose tissue, suggesting that the ECM’s composition plays a role in maintaining white adipocytes [ 121 , 122 , 123 , 124 ].…”
Section: Mechanical Regulation Of Adipogenesis and Angiogenesismentioning
confidence: 99%